2002
DOI: 10.1016/s0005-2736(02)00345-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved retention of idarubicin after intravenous injection obtained for cholesterol-free liposomes

Abstract: To date there has been a focus on the application of sterically stabilized liposomes, composed of saturated diacylphospholipid, polyethylene glycol (PEG) conjugated lipids (5-10 mole%) and cholesterol (CH) (>30 mole%), for the systemic delivery of drugs. However, we are now exploring the utility of liposome formulations composed of diacylphospholipid conjugated PEG mixtures prepared in the absence of added cholesterol, with the primary objective of developing formulations that retain encapsulated drug better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…An optimized liposomal drug delivery system should be stable under physiological conditions, yet be permeable and capable of drug release to the target site of action. Similar to our results, the incorporation of cholesterol with a liposomal formulation produced retardation in the release of doxorubicin and arabinofuranosyl cytidine (ara-C), whereas, at a higher mole percent, a much larger release rate of idarubicin was observed compared to cholesterol-free liposomes (90)(91)(92). A study by Taira et al showed that liposomes composed of egg phosphatidylcholine and cholesterol were found to be most stable within acidic gastric simulated media (pH 2) (93).…”
Section: Resultssupporting
confidence: 85%
“…An optimized liposomal drug delivery system should be stable under physiological conditions, yet be permeable and capable of drug release to the target site of action. Similar to our results, the incorporation of cholesterol with a liposomal formulation produced retardation in the release of doxorubicin and arabinofuranosyl cytidine (ara-C), whereas, at a higher mole percent, a much larger release rate of idarubicin was observed compared to cholesterol-free liposomes (90)(91)(92). A study by Taira et al showed that liposomes composed of egg phosphatidylcholine and cholesterol were found to be most stable within acidic gastric simulated media (pH 2) (93).…”
Section: Resultssupporting
confidence: 85%
“…This observation is anticipated from previous studies with cholesterol-free liposomes where a change in PEG surface density had a minor effect on liposome elimination. 43 Taken together, these data show that the lysolipid component, even in liposomes containing 5-10 mol% PEG on the surface, reduced the circulation longevity of LTSL-doxorubicin. Studies by Mills and Needham 11 suggested that lysolipid is retained during the phase transition from the gel phase to complete liquid crystalline phase upon heating the LTSL through T c .…”
Section: Functional Assessment Of Various Ltsl-doxorubicin Formulatiomentioning
confidence: 70%
“…However, the results can be compared with other studies using comparable lipid compositions (primarily DSPC and Chol) to encapsulate doxorubicin (51), vincristine (52), mitoxantrone (53), daunorubicin (54), idarubicin (55), topotecan (28), and cisplatin (56). Such a comparison clearly demonstrates that a composition that is useful for one anticancer drug may be not be of any therapeutic value for another.…”
Section: Discussionmentioning
confidence: 99%